TINDAK PIDANA PELECEHAN SEKSUAL OLEH ANAK DI BAWAH UMUR MENURUT UU NO. 35 TAHUN 2015 (Kajian Kasus di Mahkamah Syar’iyah) - Fadhilah Fadhilah (SYARIAH: Journal of Islamic Law, 2020)
AbstractProtection of children is the foundation for children to become adults in responding to future challenges. Law Number 35 of 2014 concerning child protection describes the obligation to provide protection to children, but the criminal provisions for perpetrators of child abuse, in this Law are still very weak as a basis for handling cases of abuse against children. Aceh Qanun Number 6 of 2014 concerning the law of Jinayat katagori Jarimah (sexual harassment) has been regulated in accordance with the law. The Syar'iyah Court is one of the Islamic law courts in handling children's cases. This study aims to determine the perspective of Islamic criminal law on forms of sexual abuse by minors in Law No. 35 of 2014 and Qanun No. 6 of 2014, to determine the application of criminal acts of sexual abuse by minors and to find out judges' considerations in resolving criminal acts of sexual abuse by minors. Writing using this type of qualitative research, the research location is centered at the Kuala Simpang Syar'iyah Court. The data sources obtained consist of primary data and secondary data. The data collection techniques used observation, interviews and documentation. The results showed that the perspective of Islamic criminal law on forms of sexual abuse by minors in Law No. 35 of 2014 and Qanun No. 6/2014 is a measure of the welfare and prosperity of the community, nation and state, so it is the obligation for us together with the government and every member of society to strive for child protection according to our abilities for the national interest and the interests of humanity. The application of criminal acts of sexual abuse by minors at the Kuala Simpang Syar'iyah Court still refers to Qanun No. 6 of 2014. Legal considerations of the Kuala Simpang Syar'iyah Court judges in resolving sanctions for perpetrators of sexual abuse by minors in terms of age of the child, level of action and benefit to the child.